Bahasa Makassar dalam Keluarga Urban: Antara Keakraban, Identitas dan Modernitas - St. Junaeda (INSIGHT: Indonesian Journal Social Studies and Humanities, 2026)
Abstract. The use of regional languages within urban families has become an increasingly important issue amid rapid social change, urbanization, and the growing dominance of national and global languages. As one of the local languages in South Sulawesi, the Makassar language plays a significant role in maintaining cultural values, ethnic identity, and social relationships among its speakers. However, in urban settings, language practices are often shaped by changing social aspirations, educational demands, and modern lifestyles, which influence the patterns of language transmission within families. This study examines the use of Makassar language in urban families and explores how family members negotiate its role between intimacy, cultural identity, and modernity. This research employs a qualitative approach with an ethnographic perspective to understand language practices in everyday family interactions. Data were collected through in-depth interviews, participant observation, and informal conversations with parents and children from urban Makassar families. The analysis focuses on the meanings attached to language choice, the contexts in which Makassar language is maintained or replaced, and the social factors influencing these linguistic practices. The study draws on sociolinguistic and anthropological perspectives to explain how language functions not only as a communication tool but also as a symbol of belonging and social positioning. The findings indicate that Makassar language continues to be used as a medium for expressing intimacy, emotional closeness, and kinship relations within families. At the same time, its use is increasingly negotiated with the demands of modern urban life, where Indonesian is often perceived as more beneficial for education, social mobility, and wider communication. Consequently, urban families develop diverse language strategies that reflect efforts to preserve cultural identity while adapting to contemporary social realities. The study highlights that the use of Makassar language in urban families represents an ongoing negotiation between maintaining local cultural heritage and responding to the challenges of modernity.Keywords: Makassar Language, Urban Family, Language Use, Cultural identity, modernity, Language Maintenance.